Similarities and Differences Between Ethical Codes of Conduct of AICPA and IFAC - Al-Hasan Al-Aidaros; Kamil Md. Idris; Faridahwati Mohd. Shamsudin (International Journal of Management Studies, 2015)
An accountants’ ethical code of conduct represents the moral values, principles and rules that accountants should have. The ethical codes of conduct of AICPA and IFAC are the two main codes most countries adopt to guide their members on how to deal with accounting information from the ethical perspective. While the AICPA ethical code of conduct was developed specifically for the USA, the IFAC ethical code of conduct was developed by taking into account the different practices of ethical code of conduct in various countries. The main purpose of this paper is to present an overview of the similarities and differences of these two codes. The comparison of the two documents is made on the following issues: establishment, structure and approach of the codes, the public interest principle, and the independence principle. The comparative analysis shows that the AICPA and IFAC codes are more similar than different even though some differences are noticeably important.